3D oxalato-bridged lanthanide(iii) MOFs with magnetocaloric, magnetic and photoluminescence properties. Issue 1 (30th November 2016) - Akhtar, Muhammad Nadeem; Chen, Yan-Cong; AlDamen, Murad A.; Tong, Ming-Liang
Abstract : Four isostructural 3D lanthanide(iii ) metal–organic frameworks with the general formula (H6 edte)0.5 [Ln III (ox)2 (H2 O)] (Ln = Gd (1 ), Tb (2 ), Dy (3 ) and Ho (4 ); H4 edte = N, N, N ′, N ′-tetrakis(2-hydroxyethyl)ethylenediamine) and ox = oxalate have been synthesized from oxalate. Abstract : Four isostructural 3D lanthanide(iii ) metal–organic frameworks with the general formula (H6 edte)0.5 [Ln III (ox)2 (H2 O)] (Ln = Gd (1), Tb (2), Dy (3) and Ho (4); H4 edte = N, N, N ′, N ′-tetrakis(2-hydroxyethyl)ethylenediamine) and ox = oxalate have been synthesized from oxalate. These compounds were characterized using single-crystal X-ray diffraction, FTIR and TGA/DTG. The magnetic investigation has been performed for1–4 and the results reveal that a Gd(iii ) containing MOF has the highest magnetic density and exhibits a larger cryogenic magnetocaloric effect (Δ S m = 35.9 J kg −1 K −1 for Δ H = 9 T at 2.0 K) with a high Debye temperature ( θ D = 342(3) and r D = 35). For the Dy derivative, an ac-out-of-phase signal was found, and further measurements under an applied field of 1000 Oe showed frequency-dependent out-of-phase magnetic susceptibility. Solid-state luminescence indicates that Tb and Dy-containing complexes are photoluminescent materials.